HAK WARIS ISLAM DITINJAU DARI HAM DAN KESETARAAN PERSPEKTIF NURCHOLIS MAJID - Rahman, Gazali; Andaryuni, Lilik (Islamic Family Law, STAI Sangatta Kutai Timur, 2023)
This research focuses on NurCholis Majid's perspective on inheritance rights in Islam from the standpoint of human rights and the principle of equality. NurCholis Majid is an influential Muslim intellectual in religion study and social issues in Indonesia. In NurCholis Majid's understanding, inheritance rights in Islam should see in a broader context, including the universal values of human right. According to NurCholis Majid, inheritance rights should be based on the principle in gender equality, which means granting equal rights to men and women. Although Islamic tradition tends to allocate a larger share of inheritance to men, NurCholis Majid proposes that the principle’s' quality should be uphold, thus requiring reforms in the interpretation of inheritance. He believes that fair and equal inheritance rights would be more in line with human values and the human rights. This research adopts an interdisciplinary and normative juridical approach that is qualitative. The results show that NurCholis Majid's perspective on inheritance rights in Islam emphasizes the need to integrate human rights principles and gender equality into the practice of fair inheritance. In facing social and cultural challenges, a dialogic approach and social transformation are considered the importance for achieving sustainable changes toward equal inheritance rights in Islam